2022
DOI: 10.3389/fonc.2022.841381
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of PRMT6 in Cancer

Abstract: Protein arginine methyltransferase 6 (PRMT6) is a type I PRMT that is involved in epigenetic regulation of gene expression through methylating histone or non-histone proteins, and other processes such as alternative splicing, DNA repair, cell proliferation and senescence, and cell signaling. In addition, PRMT6 also plays different roles in various cancers via influencing cell growth, migration, invasion, apoptosis, and drug resistant, which make PRMT6 an anti-tumor therapeutic target for a variety of cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 141 publications
(171 reference statements)
0
18
0
Order By: Relevance
“…Nonetheless, we should perform further investigations to understand the biological significance of targeting PRMT6 and CDC20 in combination with PRMT6 and CDC20 inhibitors to synergistically attenuate GBM cell proliferation in vitro and in vivo. In addition, PRMT6 could mediate malignant phenotypes such as cell invasion, migration, and chemotherapy resistance in tumors [18], implying that we further explore other roles and mechanisms of PRMT6 in GBM. Despite the limitations of the study, our findings highlight the PRMT6-CDC20 axis as a potentially effective target for therapeutic intervention in GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we should perform further investigations to understand the biological significance of targeting PRMT6 and CDC20 in combination with PRMT6 and CDC20 inhibitors to synergistically attenuate GBM cell proliferation in vitro and in vivo. In addition, PRMT6 could mediate malignant phenotypes such as cell invasion, migration, and chemotherapy resistance in tumors [18], implying that we further explore other roles and mechanisms of PRMT6 in GBM. Despite the limitations of the study, our findings highlight the PRMT6-CDC20 axis as a potentially effective target for therapeutic intervention in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Now, it is widely reported that PRMT6 acts as a tumor mediator and exerts a dual role in human cancer. In hepatocellular carcinoma, there is a significant correlation between decreased PRMT6 expression and short overall survival, whereas PRMT6 overexpression is associated with tumorigenicity and invasiveness in gastric cancer and lung cancer [17,18]. It has been described as an arginine methyltransferase that methylates CRAF, P16, and BAG5 proteins involved in tumor progression [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…PRMT6 upregulation has been linked to global DNA hypomethylation by impairing the chromatin binding of UHRF1, a co-factor of DNMT1, which results in passive DNA demethylation (Veland et al 2017). PRMT6 has also been shown to have a carcinogenic effect by activating the AKT/mTOR pathway in endometrial cancer and prostate cancer cells (Almeida-Rios et al 2016; Jiang et al 2020; Chen et al 2022). In various cancer cell lines, including breast, lung, colorectal, and cervical, as well as in osteosarcomas, PRMT6 was found to inhibit the expression of cyclin-dependent kinase inhibitors (CKI) p21cip1/waf1, p27kip1, and p18ink4c, or to mitigate the association of p16ink4a with CDK4.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is associated with pelvic pain and infertility, affecting 5-10% of women of childbearing age ( Taylor et al., 2021 ). Currently, the most common treatments for endometriosis are surgery and medications, but these are ineffective for many patients and carry a high risk of recurrence, causing physical and psychological pain ( Chen et al., 2022 ; Murakami et al., 2022 ). Therefore, there is an urgent need to identify the causes of endometriosis and find an effective treatment.…”
Section: Introductionmentioning
confidence: 99%